Modeling and forecasting tourism flow in Portugal: Perspectives for a strategic management - Ramos, F.R.; Lacerda, L.; Curto, J. (European Journal of Applied Business and Management, 2022)
Purpose: The increase of Tourism in Portugal, as well as the companies related to it, it is necessary to analyze and forecast the flow of tourists so that the management of the business is endowed with a competitive strategy. Given the changes in the 'recent' dynamics of tourism data, this article discusses the contributions and limitations of using classical forecasting methodologies, when applied to this sector, namely to the number of overnight stays in tourist accommodation establishments in Portugal. Methodology: The study focuses on the modeling and forecasting of time series related to the number of monthly overnight stays, in tourist accommodation establishments in Portugal, between January 2002 and March 2022. As a result of some suggestions contained in the scientific literature, it was resorted the Exponential Smoothing (ETS) methodologies. In computational terms, we used the Jupyter computational environment, with the Python programming language (version 3.7.3). Findings: The results were presented and discussed through the analysis of two time series: (1) Total number of overnight stays in tourist accommodation establishments in Portugal – Total series; (2) Number of overnight stays spent by residents in Portugal in tourist accommodation establishments in Portugal – Residents series. Overall, from the analysis of the time series, there was a growth of Tourism in Portugal since 2002, with a visible drop in 2020, due to the pandemic situation. Regarding the ETS methodologies used in the modeling and forecasting, although they corresponded positively in the forecast of the Total series (with some error), the same did not happen in the Residents series. In this series, due to the recent dynamics that are completely atypical, it appears that the ETS methodologies, potentially more adequate, do not converge, in general. However, it is important to mention that it was the overnight stays of residents that, in the pandemic period, dictated the dynamics present in the Total series. Research limitations: The literature points to a good performance of ETS methodologies in time series with characteristics present in the series under study (with the presence of a trend cycle and clear seasonality), a fact that motivated its choice. However, the difficulty of these methodologies in dealing with abrupt breaks in the data history was evident in this study. Despite how adjusted the forecasts are, the highlight is the non-convergence of some models that could be better adjusted to the historical data. In this sense, it is necessary to search for alternative forecasting methodologies, where Machine Learning methodologies, namely Deep Learning (Deep Neural Networks) have been pointed out in the scientific literature as quite promising. This will be the next step of the investigation. Originality: Given the importance that Tourism has both in the economic and social dimension of Portugal, and being a very volatile and constantly changing sector, it is imperative to define a strategy for future action to understand how, internally, the sector can define policies to avoid situations of external dependence. In addition to a current analysis of the data history, resulting from an atypical period of pandemic, we need to critically evaluate the predictive capacity of (classical) econometric models, which can be used by the industry related to tourism. This not only contributes to a better understanding of the phenomenon under study, but also constitutes a tool to support decision-making. ___ Objetivo: Com aumento do Turismo em Portugal, bem como das empresas afetas ao mesmo, impõe-se a necessidade de análise e previsão do fluxo de turistas para que a gestão dos negócios seja dotada de uma estratégia competitiva. Face às alterações na ‘recente’ dinâmica dos dados afetos ao turismo, neste artigo discutem-se os contributos e limitações do recurso às metodologias clássicas de previsão, quando aplicadas a este setor, nomeadamente ao número de dormidas em estabelecimentos de alojamento turístico em Portugal. Metodologia: O estudo incide na modelação e previsão de séries temporais afetas ao número de dormidas mensais, em estabelecimentos de alojamento turístico em Portugal, entre janeiro de 2002 e março de 2022. Decorrente de algumas sugestões constantes na literatura científica, recorreram-se às metodologias de Alisamento Exponencial (Exponential Smoothing – ETS). Em termos computacionais, foi utilizado o ambiente computacional Jupyter, com linguagem de programação Python (versão 3.7.3). Resultados: Os resultados foram apresentados e discutidos mediante a análise de duas séries temporais: (1) Número total de dormidas em estabelecimentos de alojamento turístico em Portugal – série Total; (2) Número de dormidas de residentes em Portugal em estabelecimentos de alojamento turístico em Portugal – série Residentes. Globalmente, da análise das séries temporais, verificou-se o crescimento do Turismo em Portugal desde 2002, com uma quebra visível em 2020, decorrente da situação pandémica. Relativamente às metodologias ETS utilizadas na modelação e previsão, embora estas tenham correspondido de forma positiva na previsão da série Total (embora com algum erro), o mesmo não se verificou na série Residentes. Nesta série, por ter uma dinâmica recente completamente atípica (os dados históricos não replicam o comportamento atual) verifica-se que os modelos ETS, potencialmente mais adequados (com componente de tendência e sazonalidade), não convergem, em geral. Contudo, importante será referir que foram as dormidas dos residentes que, no período pandémico, ditaram a dinâmica presente na série Total. Limitações: A literatura aponta para um bom desempenho das metodologias ETS em séries temporais com características presentes nas séries em estudo (com presença de um ciclo de tendência e clara sazonalidade), facto que motivou a sua escolha. Contudo, a dificuldade destas metodologias em lidar com quebas abruptas de estrutura, no histórico dos dados, ficou patente neste estudo. Não obstante de previsões mais ou menos ajustadas, o destaque vai para a não convergência de alguns modelos que, em certa medida, se poderiam ajustar melhor ao histórico de dados. Neste sentido, impõe-se a procura de metodologias de previsão alternativas, onde as metodologias de Machine Learning, nomeadamente Deep Learning (Deep Neural Networks) têm sido apontadas na literatura científica como bastante promissoras. Esse será o caminho seguinte de investigação. Originalidade: Face à importância que o Turismo tem no tecido económico e social em Portugal, dado que se trata de um setor bastante volátil e em constante mudança, impõese a definição de uma estratégia de atuação futura para perceber como, internamente, o sector pode definir políticas por forma a evitar situações de dependência externa. Para tal, além de uma análise atual ao histórico de dados, decorrente de um período atípico de pandemia, impõem-se avaliar de forma crítica a capacidade preditiva de modelos econométricos (clássicos), passíveis de serem utilizados pela indústria afeta ao turismo. Tal contribui não só para um melhor entendimento do fenómeno em estudo, como constitui uma ferramenta de apoio à tomada de decisão.